Examining the incentive effects of athlete compensation: a combined analysis using SEM and fsQCA - Zhao, Huan; Chong, Hebin; Xiao, Feiyan; Tan, Li; Liu, Zhaoxia (Frontiers in Psychology, 2024)
In the context of competitive sports, the evaluation of compensation incentive effectiveness is key to the optimization of compensation systems for athletes.This study creates a model of the athlete compensation incentive effect from single and multinomial grouping perspectives, combining empirical research (SEM) with fuzzy-set qualitative comparative analysis (fsQCA) based on a sample of 352 validated data. The results lead to two findings. First, athletes' direct economic compensation, direct non-economic compensation, and indirect non-economic compensation have a significant positive effect on the incentive effect of compensation. Second, that the incentive effect of high compensation has two configurations, namely "economic value" and "economic environmental value". It seems that the effective combination of compensation factors can enhance the motivation effect in a "different way".